Aberration detection of pertussis from the Mazandaran province, Iran, from 2012 to 2018: Application of discrete wavelet transform - Yousef Alimohamadi (Journal of Acute Disease, 2020)
Objective: To define the level of alarm threshold for pertussis aberrations and to detect the aberrations of the reported suspected cases of pertussis from the Mazandaran province in the north of Iran. Methods: The included cases were composed of the suspected pertussis patients who came from Mazandaran province and registered in the Center for Disease Control and Prevention from 20 March 2012 to 20 March 2018. A discrete wavelet transform- based method was used to detect the aberrations. All analyses were performed using MATLAB Software version 2018a and Excel 2010. Results: A total of 1 162 cases were recruited in the study, including 545 (46.90%) males and 617 (53.10%) females, with median age of 1.47 (0.22-9.56) years. The median age of males was 1.18 (0.21-8.24) years, while that of females was 1.82 (0.21-10.75) years. Concerning the level of the alarm threshold, it was 1.28 case/d when k=2, while it was 1.34 case/d when k=3. The total detected aberration days were 123 d and 57 d by considering k=2 and 3, respectively. The most defined alarm threshold was related to spring (>2 cases/d) and summer (>1 case/d), respectively. Conclusions: The sensitivity of the surveillance system is subjected to a different time. Thus, determining the level of alarm threshold periodically using different methods is recommended.